Faktor-faktor yang Memengaruhi Pengambilan Keputusan Petani dalam Program Replanting (Peremajaan) Kelapa Sawit Swadaya di Kabupaten Sekadau, Kalimantan Barat - Rulianawati, Nia; Hutajulu, Josua Parulian; Aritonang, Marisi (Universitas Galuh, 2024)
Oil palm rejuvenation is the process of planting young seedlings in place of 20–25-year-old oil palm trees. Old oil palm trees are unproductive and lose productivity every month, which is why this is done. The purpose of this study is to ascertain the degree to which farmers freely decide whether to replant oil palm and the variables influencing these decisions. This study employs a quantitative methodology that includes documentation, questionnaire-based interviews, and observation. In the independent oil palm rejuvenation initiative, the degree of farmer decision-making and the factors influencing farmer decision-making are assessed using logistic regression analysis. As a result, the autonomous oil palm rejuvenation program's level of farmer decision-making is 1, meaning that farmers are carrying out the program. Regression analysis is then performed once everything is finished. In the oil palm rejuvenation initiative in Sekadau Regency, West Kalimantan, farmers' decision-making is heavily influenced by a number of factors, including their income, degree of education, and participation in extension activities. Age, the number of dependents, and land area are not very essential considerations.